St. Vincent and the Grenadines development plan 1986-1988 : first annual update 1987-89 (Ministry of Finance and Planning. Central PlanningDivision KingstownVC, 1987)
Reviews economic performance for the period 1985-86. Outlines macroeconomic projections and public sector investment programme for 1987-89. Reviews the 1986 performance of eleven sectors of the economy and examines new policies and programmes relating to these sectors planned for 1987-89. Sectors include agriculture, manufacturing, trade, energy, tourism, transport, education, water supply, housing, and social development. Describes the administrative organization for planning and plan implementation. Stresses importance of manpower planning.
IDS